An Empirical Evaluation of Repeatable Testing as a Technique for Improving Management Education - Parke, E. Lauck; Schermerhorn, John R.; Shirland, Larry E. (Academy of Management Journal, 1981)
The article presents information on a study that investigated an empirical evaluation of repeatable testing as a means of improving management education. Repeatable testing gives students the opportunity to take a test, receive feedback, engage in additional study, and then take another test to measure performance improvement. The theory behind the practice considers feedback to be a performance incentive. The authors tested the hypothesis by questioning 125 students enrolled in an introductory course in organizational behavior. Results showed that those tested more than once did score better on the average than those who were only tested once, but the results were not statistically significant.